PicASHOW pictorial authority search by hyperlinks on the web. - Lempel, Ronny (ACM transactions on information systems.)
We describe PicASHOW, a fully automated WWW image retrieval system that is based on several link-structure analyzing algorithms. Our basic premise is that a page p displays (or links to) an image when the author of p considers the image to be of value to the viewers of the page. We thus extend some well known link-based WWW page retrieval schemes to the context of image retrieval.PicASHOW's analysis of the link structure enables it to retrieve relevant images even when those are stored in files with meaningless names. The same analysis also allows it to identify image containers and image hubs. We define these as Web pages that are rich in relevant images, or from which many images are readily accessible.PicASHOW requires no image analysis whatsoever and no creation of taxonomies for preclassification of the Web's images. It can be implemented by standard WWW search engines with reasonable overhead, in terms of both computations and storage, and with no change to user query formats. It can thus be used to easily add image retrieving capabilities to standard search engines.Our results demonstrate that PicASHOW, while relying almost exclusively on link analysis, compares well with dedicated WWW image retrieval systems. We conclude that link analysis, a proven effective technique for Web page search, can improve the performance of Web image retrieval, as well as extend its definition to include the retrieval of image hubs and containers.